APLIKASI KOMPOS SEBAGAI PEMBENAH PADA BAHAN INDUK TANAH TAMBANG EMAS DI DESA TATELU KECAMATAN DIMEMBE - Yohanes Sunuk; Maria Montolalu; Zetly E. Tamod (COCOS, 2017)
ABSTRACT Compost is a product of decomposition of organic materials accelerated by various microbes to become weathered. This study aims to examine the change of soil chemical properties of the gold mine soil before and after the application of soil composting materials. The research method used is descriptive from the analysis of soil chemical properties such as : Color, pH, C-Organic, N, P, and K. Parent material of gold mine soil generally have pale yellow color, low pHÂ  (acid), C-organic , N, P, and K are not ideal or low. The condition of the mine ground material is in the phase of damage. Soil ameliorant are natural or synthetic materials used to cope with soil damage. Compost is one of the organic soil ameliorant with the function of improving the condition of damaged soil and also as a source of nutrients. Compost will give changes to the gold mine soil material but not quickly, it takes a relatively long time. Â Keywords: Compost, Soil ameliorant, Material of Gold Mine Ground.